Republic of Mozambique : Financial Sector Assessment program-Financial System Stability Assessment. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This paper discusses key findings of the Financial System Stability Assessment (FSSA) for the Republic of Mozambique. As a result of a comprehensive financial sector reform program largely based on the 2003 Financial Sector Assessment Program recommendations, Mozambique has made significant progress toward developing and strengthening the banking sector, enhancing supervision, and improving central bank operations. However, despite several government initiatives and legal and regulatory reforms, progress in financial deepening and access has been less satisfactory.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet